The effect of Garcinia livingstonei aqueous leaf extract on hyperglycaemic-induced human sperm cell: An in-vitro study - Murendeni Nethengwe; Kunle Okaiyeto; Chinyerum S. Opuwari; Oluwafemi O. Oguntibeju (Phytomedicine Plus)
Hyperglycaemia is the main instigator of the development of male infertility in men with diabetes mellitus (DM). The consequent production of excessive reactive oxidative species (ROS) and a compromised antioxidant defence system leads to testicular damage and a decline in sperm parameters. Supplementation with antioxidants sourced from medicinal plants is beneficial in the treatment of DM-related male infertility. However, a search for more efficacious and easily accessibly medicinal plants is paramount. Garcinia livingstonei is a well-known and accessible medicinal plant used in traditional practices for the treatment of diabetic complications. However, very scarce information on the plant extract's potential benefits exists in the literature. The current study investigated the effect of aqueous leaf extract of G. livingstonei on hyperglycaemic human male sperm cell parameters. Hyperglycaemia was induced using sperm media supplemented with 100 mM D-glucose over 24 h. Hyperglycaemia induction led to a significant (P<0.05) decline in sperm motility, vitality, DNA integrity, mitochondrial membrane potential (MMP), and acrosome integrity. The effect of the plant extract on spermatozoa was concentration-dependent, with the lowest concentration demonstrating the highest protective effects. A significant (P<0.05) improvement in all tested sperm parameters was observed after exposure of the hyperglycaemic spermatozoa to aqueous leaf extract of G. livingstonei. The effect of acarbose on all tested sperm parameters was comparable to that of the plant extract. The findings of this study suggest the potential therapeutic effect of G. livingstonei in the treatment of DM-related male infertility. However, the use of an appropriate dosage depending on the pathological target is paramount.